1998
DOI: 10.1046/j.1365-2648.1998.00573.x
|View full text |Cite
|
Sign up to set email alerts
|

Perceived social support and community adaptation in schizophrenia

Abstract: Prompted by the continuing transition to community care, mental health nurses are considering the role of social support in community adaptation. This article demonstrates the importance of distinguishing between kinds of social support and presents findings from the first round data of a longitudinal study of community adaptation in 156 people with schizophrenia conducted in Brisbane, Australia. All clients were interviewed using the relevant subscales of the Diagnostic Interview Schedule to confirm a primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
6
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 42 publications
4
6
0
Order By: Relevance
“…They also long for empathy and for a positive attitude to be taken towards them. The present study supports previous research that has highlighted the deficits in emotional support for people with chronic mental illness (Bronowski & Załuska, 2008;Clinton, Lunney, Edwards, Weir, & Barr, 1998). Furthermore, the impact of stigma upon individuals with mental disorders is multi-faceted and devastating.…”
Section: Discussionsupporting
confidence: 90%
“…They also long for empathy and for a positive attitude to be taken towards them. The present study supports previous research that has highlighted the deficits in emotional support for people with chronic mental illness (Bronowski & Załuska, 2008;Clinton, Lunney, Edwards, Weir, & Barr, 1998). Furthermore, the impact of stigma upon individuals with mental disorders is multi-faceted and devastating.…”
Section: Discussionsupporting
confidence: 90%
“…They reported no access to friends with whom they could share happiness, feel confidence or appreciation. These results support the findings by Clinton et al . (1998) whose research explored the social network and community adaptation of people with schizophrenia.…”
Section: Schizophrenia and Relationshipssupporting
confidence: 93%
“…Continuity of care by staff and ongoing involvement in supportive activities both before and after the move reduces relocation trauma and promotes a more successful transition (Farhall et al, 2003). Clinton, Lunney, Edwards, Weir, Barr (1998) recommended that treatments focus on assisting consumers to build their social networks, access social support and promote a positive perception of their life, as this will facilitate competence, improve their ability to cope with stress and achieve community adaptation. Clinton et al reported that consumers with larger and more supportive social networks are admitted to hospital less frequently.…”
Section: Occupational Needs Of Clients In Etru/ccu Settingsmentioning
confidence: 99%